(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Negative appendectomy, defined as the removal of a histologically normal appendix, remains a measurable source of avoidable morbidity. It is difficult to identify patients with a very low probability of true appendicitis before committing them to surgery. The aim of this study was to determine the institutional incidence of negative appendectomy and identify clinical, biochemical, as well as imaging and scoring parameters able to discriminate these patients. Methods: This was a retrospective observational study done in Indira Medical College and Hospitals, covering a three-year period from October 2022 to October 2025 for all patients undergoing appendectomies. Two hundred and twenty patients were found to meet the eligibility criteria for the study. Histopathological examination of resected specimen constituted the diagnostic gold standard, while clinical scoring (Alvarado and Appendicitis Inflammatory Response [AIR] scores) was calculated. Independent samples t-test, Fisher’s exact test and Mann–Whitney U analysis were employed for statistical inference. A p-value of <0.05 was considered statistically significant in a two-tailed test. Results: Of the cases, five (2.27%; 95% CI: 0.30%–4.24%) found on final histopathology to have a histologically normal appendix constituted the negative appendectomy group. Compared to confirmed appendicitis, patients undergoing negative appendectomy had significantly lower leucocyte counts (8,587.2 ± 1,289.8 vs 14,926.6 ± 2,344.0 cells/μL; p < 0.001), a lower percentage of neutrophils (59.0 ± 4.2% vs 83.1 ± 5.2%; p < 0.001), and lower C-reactive protein (10.4 ± 3.4 vs 54.5 ± 19.9 mg/L; p < 0.001). Alvarado scores for all negative cases ranged 5 to 6, while they ranged 8.4 ± 1.1 in the positive group (p < 0.001). AIR scores ranged from 3 to 5 in all negative cases and was higher in positive patients at 10.2 ± 1.4, (p < 0.001). Ultrasonography was positive for appendicitis in all confirmed cases, but positive in negatives (p < 0.001). No statistical significance was picked for simply age and sex. Conclusion: A negative appendectomy rate of 2.27% augurs well for the institute. Lower clinical scores (Alvarado ≤6, AIR ≤5), only modest leucocytosis with mild neutrophilia, near normal CRP and absence of sonographic evidence of appendicitis are the most robust measurable predictors of unnecessary appendectomy. The addition of mandatory scoring threshold with cross-sectional imaging for equivocal cases is believed to hold significant value to eliminating the residual negative appendectomy rate.